Hubungan Frekuensi Konsumsi Kopi dengan Kualitas Tidur Mahasiswa Fakultas Kedokteran Universitas Islam Bandung - Hana Badiiah; A. Rahmah Furqaani; A. Kartika Sari (Bandung Conference Series: Medical Science, 2023)
Abstract. Coffee is the second largest drink in the world that is produced and consumed and contains several types of compounds, namely caffeine, potassium and polyphenols, so it is often referred to as an addictive substance. The aim is to analyze the relationship between the frequency of coffee consumption and the quality of sleep of students at the Faculty of Medicine, Bandung Islamic University. This study used an analytic observational method with a retrospective cohort study design. The research was conducted in October. Data was obtained by distributing questionnaires to respondents from the Faculty of Medicine, Bandung Islamic University online. The statistical test used the data collected and then tested using the Chi-Square statistical test to analyze whether or not the relationship between the independent and dependent variables was tested. The number of respondents in this study were 227 people. The results of the study showed that 227 respondents, more rarely consumed coffee, namely around 142 people who consumed coffee (62.6%), 69 people (30.4%) consumed coffee in the moderate category and 16 people (7.0%) drink coffee often. The results showed that the frequency of coffee consumption with the sleep quality of students at the Faculty of Medicine, Bandung Islamic University was not significant (not significant). There are other factors that must be investigated on the quality of sleep among medical students. Abstrak. Kopi menjadi minuman terbesar kedua di dunia yang diproduksi serta dikonsumsi dan mengandung beberapa jenis senyawa yaitu kafein, kalium, dan polifenol sehingga sering disebut sebagai zat adiktif. Tujuan menganalisis hubungan frekuensi konsumsi kopi dengan kualitas tidur mahasiswa fakultas kedokteran universitas islam bandung. Penelitian ini menggunakan metode observasional analitik dengan rancangan penelitian kohort retrospektif. Penelitian dilaksanakan bulan Oktober. Data diperoleh dengan penyebaran kuesioner terhadap responden mahasiswa fakultas kedokteran universitas islam bandung secara online. Uji statistik menggunakan uji data yang terkumpul kemudian diuji menggunakan uji statistik Chi-Square untuk menganalisis ada tidaknya hubungan antara variable bebas dan terikat. Jumlah responden pada penelitian ini sebanyak 227 orang. Didapatkan hasil penelitian, 227 orang responden, lebih banyak yang jarang mengonsumsi kopi yaitu sekitar 142 orang yang mengonsumsi kopi (62,6%), 69 orang (30.4%) mengonsumsi kopi dengan kategori sedang dan 16 orang (7.0%) sering minum kopi. Hasil penelitian menunjukkan frekuensi konsumsi kopi dengan kualitas tidur mahasiswa fakultas kedokteran universitas islam bandung tidak signifikan (tidak bermakna). Terdapat faktor lain yang harus diteliti terhadap kualitas tidur di kalangan mahasiswa fakultas kedokteran.